2018
DOI: 10.1155/2018/6205140
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Sound Quality of Steady and Unsteady Exhaust Noise

Abstract: In order to predict and study the sound quality of automobile exhaust noise, Zwicker steady-state and time-varying method were applied to calculate the psychoacoustic objective parameter values in terms of the exhaust noise of sample cars at uniform velocity and accelerated velocity; Thereby, a prediction model of GA-BP sound quality based on psychoacoustic objective parameters was established. At the same time, wavelet analysis was used to decompose the accelerated signal; in order to overcome the shortcoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Zeng, FL. et al [ 30 ] used the ZSSTV method to establish a GA-BP sound prediction model, based on objective parameters and a sound quality parameter SQP-WRW. Their test results demonstrated that the model enjoyed higher accuracy in predicting the quality.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng, FL. et al [ 30 ] used the ZSSTV method to establish a GA-BP sound prediction model, based on objective parameters and a sound quality parameter SQP-WRW. Their test results demonstrated that the model enjoyed higher accuracy in predicting the quality.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a comparison of relevant aspects between present and past factors was carried out to verify the value of the proposed index. Zeng and Sun 27 took the advantage of the Zwicker steady-state time-varying method to predict a sound quality on the basis of psychoacoustic parameters, through which a new sound quality parameter, SQP-WRW (sound quality parameter base on wavelet and then proceed to RNR-WVD), was developed. The SQP-WRW-based model enjoyed benefits of the improvement of accuracy in prediction for the sound quality when the signal of acceleration was sent out.…”
Section: Introductionmentioning
confidence: 99%
“…Its psychoacoustic objective parameters are timevarying and fluctuate drastically; thus, they cannot be calculated based on the frequency domain model [11]. In addition, the time domain or frequency domain analysis alone cannot accurately reflect the characteristics of vehicle noise, so the time domain and frequency domain signal features should be studied and extracted simultaneously [12]. Wang found that the traditional frequency-based techniques were not applicable to sound quality evaluation (SQE) in the case of the nonstationary vehicle noises [13].…”
Section: Introductionmentioning
confidence: 99%